Approaches for increasing the lifetime of single-shot coils. Issue 1 (20th January 2020) - Schubotz, Stefan; Nacke, Bernard
Abstract : Purpose: The purpose of this study is now to optimize the coil in a way that its lifetime is increased. In the industry, induction hardening of rotationally symmetrical workpieces in a single-shot process is a common method. Owing to only partial superimposition of the workpiece areas to be heated by the inductor, high power densities are frequently needed there. These lead to local hot spots, amounting to an intensive material stress in the copper and often result in short lifetime of the inductor. Design/methodology/approach: In this elaboration, some numerically analysed approaches are presented that can be used to reduce mechanical stresses in the single-shot inductor and thus increase the service life. Findings: It has been found out that changing the coil profiles has a strong influence on its lifetime. Besides that, the heat transfer coefficient between coil and coolant plays a big role and needs to be considered when the coil is dimensioned. Originality/value: The lifetime of the coil is an important factor and often requested from the customers. Broken coils create a lot of extra costs and can generate downtime. Therefore, many customers that are struggling with thermal fatigue are interested in approaches that prolong the coil lifetime.